The Potential Impact of Climate Change on Soil Properties and Processes and Corresponding Influence on Food Security - Brevik, Eric C. (My University, 2013)
According to the IPCC, global temperatures are expected to increase between 1.1 and 6.4 °C during the 21st century and precipitation patterns will be altered. Soils are intricately linked to the atmospheric/climate system through the carbon, nitrogen, and hydrologic cycles. Because of this, altered climate will have an effect on soil processes and properties. Recent studies indicate at least some soils may become net sources of atmospheric C, lowering soil organic matter levels. Soil erosion by wind and water is also likely to increase. However, there are many things we need to know more about. How climate change will affect the N cycle and, in turn, how that will affect C storage in soils is a major research need, as is a better understanding of how erosion processes will be influenced by changes in climate. The response of plants to elevated atmospheric CO2 given limitations in nutrients like N and P, and how that will influence soil organic matter levels, is another critical research need. How soil organic matter levels react to changes in the C and N cycles will influence the ability of soils to support crop growth, which has significant ramifications for food security. Therefore, further study of soil-climate interactions in a changing world is critical to addressing future food security concerns.
Keywords: climate change; food security; soil properties; soil processes; soil health/quality